2006
DOI: 10.1128/jvi.01645-06
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated Influenza Virus Expressing Human Interleukin-2 Reveals Increased Immunogenic Potential in Young and Aged Hosts

Abstract: Despite the reported efficacy of commercially available influenza virus vaccines, a considerable proportion of the human population does not respond well to vaccination. In an attempt to improve the immunogenicity of live influenza vaccines, an attenuated, cold-adapted (ca) influenza A virus expressing human interleukin-2 (IL-2) from the NS gene was generated. Intranasal immunization of young adult and aged mice with the IL-2-expressing virus resulted in markedly enhanced mucosal and cellular immune responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 68 publications
1
30
0
Order By: Relevance
“…Although we show proof of principle that at least three SIV-specific CD8 T-cell responses (one Gag response and two Tat responses, all presented by Mane-A*10) can be boosted simultaneously by this recombinant influenza virus strategy, it could be cumbersome to construct sufficient numbers of influenza virus vectors to broadly cover relevant HIV/SIV T-cell epitopes in outbred populations. Expression of whole heterologous proteins from influenza virus proteins is technically possible and has been achieved with expression of the enhanced green fluorescence protein, interleukin-2, and tuberculosis proteins (21,37,56); however, the stability of such vectors will require careful study. We are currently constructing influenza virus vectors expressing whole SIV proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although we show proof of principle that at least three SIV-specific CD8 T-cell responses (one Gag response and two Tat responses, all presented by Mane-A*10) can be boosted simultaneously by this recombinant influenza virus strategy, it could be cumbersome to construct sufficient numbers of influenza virus vectors to broadly cover relevant HIV/SIV T-cell epitopes in outbred populations. Expression of whole heterologous proteins from influenza virus proteins is technically possible and has been achieved with expression of the enhanced green fluorescence protein, interleukin-2, and tuberculosis proteins (21,37,56); however, the stability of such vectors will require careful study. We are currently constructing influenza virus vectors expressing whole SIV proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have focused on the use of cytokines as intranasal vaccine adjuvants to enhance the immunogenicity of the DNA vaccine because of their potent effects on innate and adaptive immunity as well as functional diversity of immune responses. Studies have shown that cytokines, such as IL-12 [13,14] , IL-2 [15] , IL-15 [16] , type I interferon (IFN) [17,18] , IL-1 [19] , IL-6 [20] , and granulocyte-macrophage colony-stimulating factor (GM-CSF) [21] , enhanced antigen-specific immunity following delivery with different antigens.…”
Section: Introductionmentioning
confidence: 99%
“…In this group, cytokines, especially interleukin 2 (IL2), have proved to enhance the immunogenicity and protective efficacy of inactivated influenza vaccines [1,4]. In a previous study, we demonstrated that a cold-adapted (ca) influenza A virus vector co-expressing human IL2 (hIL2) boosted the mucosal IgA and cellular immune response as well as the protection rate after wildtype (wt) influenza virus challenge of aged mice to levels of young mice immunized with a non-IL2-expressing control virus [9].…”
Section: Introductionmentioning
confidence: 98%